Fluorescent labeling as a strategy to evaluate uptake and transport of polymeric nanoparticles in plants - Proença, Patrícia L.F. [UNESP]; Carvalho, Lucas B. [UNESP]; Campos, Estefânia V.R. [UNESP]; Fraceto, Leonardo F. [UNESP] (Elsevier, 2022)
The use of biodegradable nanopolymers in agriculture offers an excellent alternative for the efficient delivery of agrochemicals that promote plant protection and development. However, tracking of these systems inside plants requires complex probe tagging strategies. In addition to providing a basis for better understanding such nanostructures to optimize delivery system design, these probes allow monitoring the migration of nanoparticles through plant tissues, and determine accumulation sites. Thus, these probes are powerful tools that can be used to quantify and visualize nanoparticle accumulation in plant cells and tissues. This review is an overview of the methods involved in labeling nanocarriers, mainly based on polymeric matrices, for the delivery of nanoagrochemicals and the recent advances in this field.
Keywords: Chemical uptake; Fluorescent probe; Nanoparticles; Plants; Translocation